Delegating for business success - Chan, Janis Fisher (American Management Association, 2004)
Empower staff and the organization with savvy delegation skills for 21st-century success. Delegation has always been an essential supervisory and managerial competency. In today's lean, competitive workplace, it's a survival skill for organizational success. This lively new look at an old skill addresses today's delegation challenges with a workable plan and many practical exercises to ensure successful implementation. Discover what delegating really involves and learn to make confident delegating choices. Readers will learn how to: Respond rapidly to changing circumstances and employ time an.